2021
DOI: 10.1200/po.20.00522
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Profiling From Breast Cancer Screening Through to Metastatic Disease

Abstract: PURPOSE We investigated the utility of the Oncomine Breast cfDNA Assay for detecting circulating tumor DNA (ctDNA) in women from a breast screening population, including healthy women with no abnormality detected by mammogram, and women on follow-up through to advanced breast cancer. MATERIALS AND METHODS Blood samples were taken from 373 women (127 healthy controls recruited through breast screening, 28 ductal carcinoma in situ, 60 primary breast cancers, 47 primary breast cancer on follow-up, and 111 metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Nowadays multiple biomarkers, such as circulating miRNA (Baldasici et al, 2022), circulating tumor DNA (Page et al, 2021) and circulating tumor cell (Ring et al, 2022), can be used to detect metastasis of BC. What's more, several serum biomarkers related to metastasis, including soluble POSTN (Jia et al, 2022), PTHrP (Washam et al, 2013), S100P (Peng et al, 2016), have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays multiple biomarkers, such as circulating miRNA (Baldasici et al, 2022), circulating tumor DNA (Page et al, 2021) and circulating tumor cell (Ring et al, 2022), can be used to detect metastasis of BC. What's more, several serum biomarkers related to metastasis, including soluble POSTN (Jia et al, 2022), PTHrP (Washam et al, 2013), S100P (Peng et al, 2016), have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays multiple biomarkers, such as circulating miRNA 30 , circulating tumor DNA 31 and circulating tumor cell 32 , can be used to detect metastasis of breast cancer. What's more, several serum biomarkers related to metastasis,including soluble POSTN 33 , PTHrP 34 , S100P 35 ,have been found.…”
Section: Discussionmentioning
confidence: 99%
“…In serial monitoring of variants detected, changes in the allele frequency of PIK3CA and TP53 mutations were reflective of response to chemotherapy [ 54 ]. In a report with 373 women including healthy controls (N = 127), ductal carcinoma in situ (N = 28), primary breast cancers (N = 60), primary breast cancer on follow-up (N = 47), and metastatic breast cancers (N = 111) using the Oncomine Breast Cancer cfDNA assay, ESR1 , TP53 , and PIK3CA mutations accounted for 93% of all variants detected and predicted poor overall survival (OS) in mBCa [ 55 ].…”
Section: Methods For the Detection Of Circulating Tumor Dnamentioning
confidence: 99%